How antitrust failed workers - Posner, Eric A., 1965- (New York, NY : Oxford University Press, 2021)
Antitrust laws are traditionally used to attack monopolies like Facebook and Google who are able to either charge high prices or degrade the quality of their services because customers cannot switch to competitors. Antitrust laws are also used to attack cartels of businesses, which fix prices. In recent years, it has become clear that firms with market power not only charge higher prices. They also suppress wages, injuring workers. In this book, Eric Posner describes how workers can use antitrust law to counter employer market power and obtain higher wages as a result.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 9, 2021).
Keywords: Antitrust law -- Economic aspects -- United States; Labor economics -- United States